Advances of magnetocardiography in application of adult and fetal cardiac diseases - Li, Junting; Shen, Yaqian; Shen, Chengxing; Ning, Xiaolin; Xiang, Min (Frontiers in Cardiovascular Medicine, 2025)
Magnetocardiography (MCG) is a highly sensitive, non-invasive, and functional imaging technique that records and examines magnetic fields generated by the electrical activity of the heart to reflect cardiac electrophysiological changes, including the first superconducting quantum interference device and optically pumped magnetometers-MCG. The 60-year research process yields new understanding in the areas of signal extraction, processing, and clinical application for the detection and treatment of cardiac diseases. Especially, the significant advancements in magnetic sensor technology, preprocessing methods and denoising methods have promoted the development of MCG. This article systematically reviews 83 studies to provide the latest and general overview of MCG in acute chest pain (6 studies), acute coronary syndrome (10 studies), ischemic heart disease (13 studies), non-ischemic cardiomyopathies (3 studies), arrhythmia (9 studies), and fetal congenital arrhythmia (11 studies). We highlight its incremental value in the triage of acute chest pain, diagnosis and prognosis prediction of chronic and acute coronary syndromes. We also discuss the limitations of this field and directions of future development.